Power electronics : converters, applications, and design - Mohan, Ned (John Wiley & Sons, 2003)
This text describes a variety of practical and emerging power electronic converters made feasible by the new generation of power semiconductor devices. Topics include an expanded discussion of diode rectifiers and thyristor converters as well as chapterson heat sinks and magnetic components.